Simulating turning cycles on CNC lathe machines - Юрій Володимирович Петраков; Джон Мару Езендука (Mechanics and Advanced Technologies, 2022)
It is shown that the turning of the contour shaped surfaces of parts is mainly carried out according to the cycles of rough turning G71, G72, G73 with a finishing pass according to the cycle G70. In any case, the cutting process is quasi-stationary, which determines the need to control the cutting mode to stabilize and optimize the process. It is proposed to use a special program for designing the control program of a CNC machine tool, which, based on a priori information about the technological machining system, performs the simulation of the process. During simulation, in the process of solving the optimization problem according to the criterion of maximum Material Removal Rate, all components of the cutting mode are automatically determined: depth, feed and spindle speed. The results are presented in the form of control files, according to which a control program in G-codes can be compiled to optimize the process. In addition, it is additionally possible to obtain a prediction about the actually machined contour, taking into account the elastic deformation during the cutting process, and data on the correction of the trajectory of the shaping movement in the last pass.